Peran Guru dalam Pemanfaatan Media WAG untuk Meningkatkan Pembelajaran di Masa Pandemi Covid-19 - Ika Ritaria Oktriana; Victor Novianto (UM Purwokerto Press, 2022)
The COVID-19 pandemic has affected all aspects of life. One of them is in the field of education. Teachers must be able to use technology to improve learning during the COVID-19 pandemic. Learning activities must continue to prioritize educational goals, namely integrating knowledge, skills, attitudes, and mastery of technology. Online learning is an alternative that can overcome these problems. In the midst of the Covid-19 pandemic, teaching and learning activities are endeavored to use innovative online learning media. Various media can be used to carry out online learning. This study aims to explain the role of teachers in the use of online learning technology during the Covid-19 pandemic. This study uses a qualitative approach. The research method used is literature study. The results showed that the teacher's role in the use of WhatsApp Group media could improve learning during the Covid-19 pandemic. In an effort to support the continuity of the education and learning process, WhatsApp Group can be used as a learning medium, so that learning can take place without being limited by space and time. WhatsApp Group is one of the easy online learning media and provides online classes through the group chat feature. By using WhatsApp Group educators can provide encouragement to arouse, stimulate, and increase students' learning motivation, so that learning objectives can be achieved properly. . Through the WhatsApp Group application, a teacher can provide material briefly to students.